130 PATIENT-TAILORED OUTPATIENT CHEMOTHERAPY REGIMENS FOR METASTATIC COLORECTAL CANCER. (10th December 2015) - Uckun, F. M.; Morar, S.; Lundell, K.; Eddy, L.; Olson, P.; Larson, J.; Qazi, S.
Abstract : Background: We treated 62 patients with advanced Stage IV colorectal cancer in an outpatient setting with multiple cycles of Xeloda-based empirical chemotherapy regimens ("Xeloda regimens"), including Xeloda monotherapy, Xeloda + irinotecan, Xeloda + oxaliplatin, and Xeloda + mitomycin. Of these 62 patients, 15 were not previously treated with a 5-fluorouracil (5-FU)-containing regimen, while 47 had failed one (N = 21) or more (N = 26) treatments, including at least one 5-FU containing regimen. Methods: Fusion technology with combined anatomic and functional imaging using CT/MRI scans fused with whole body PET scans along with serial cancer marker level measurements was employed to monitor response to therapy and tailor the treatments to each patient according to their treatment response. Patients who showed evidence of progression on a given Xeloda regimen were switched to a different Xeloda regimen. Results: Failure to respond to a particular Xeloda regimen did not preclude objective responses to a different Xeloda regimen. For the 15 5-FU-naive patients, the median survival was 16 months. Of the 47 patients who were previously treated with at least one 5-FU regimen, 37 (79%) died at a Kaplan-Meier calculated median of 10 months (95% CI 9-15 months; log normal mean ± SD = 11.4 ± 2 months). The remaining 10 patients (21%) are alive, surviving progression-free at 7 months, 12 months (N = 3), 15 months, 16 months, 17 months, 26 months, 27 months, and 30 months, respectively, with a median progression-free survival time of > 15 months. No patient was hospitalized because of treatment-related complications. Our results demonstrate that a significant portion of previously treated Stage IV colorectal cancer patients with liver, lung, and/or brain metastases can achieve long-term progression-free survival with an excellent quality of life on empirical Xeloda-based outpatient treatments. By comparison, the overall average of the median survival times for 449 Stage IV colorectal cancer patients treated on a clinical trial arm from 8 major published clinical studies was 10.9 months. Conclusions: Fusion technology provides medical oncologists with a powerful diagnostic tool for timely termination or modification of ineffective treatments. Patients with advanced colorectal cancer should be offered empirical patient-tailored chemotherapy as an alternative to the clinical trial and hospice options.